2013
DOI: 10.11118/actaun201361061907
|View full text |Cite
|
Sign up to set email alerts
|

Fin condition of fish kept in aquacultural systems

Abstract: KLÍMA ONDŘEJ, KOPP RADOVAN, HADAŠOVÁ LENKA, MAREŠ JAN: Fin condition of fi sh kept in aquacultural systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…In our study, SD was the only factor that did not have an effect on the level of fin damage. This finding conforms to other research that there is no relationship between SD and the level of fin damage (3,6,7,9,32). The normal recommended SD for rainbow trout is 2 -80 kg/m 3 (26).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, SD was the only factor that did not have an effect on the level of fin damage. This finding conforms to other research that there is no relationship between SD and the level of fin damage (3,6,7,9,32). The normal recommended SD for rainbow trout is 2 -80 kg/m 3 (26).…”
Section: Discussionsupporting
confidence: 78%
“…There is a significant body of experimental research which identified that the main factors affecting fin damage are feeding practices, water quality, stocking density and routine handling, not excluding the bacterial infections (3,6,7,8,9). However, despite the experimental approach, there are few research reports that determine the important factors having effect on fin damage and fish welfare under different commercial production systems (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to (chronic) stress suboptimal management can result in external morphological damage of the eyes, skin and fins, as well as in deformities and emaciation of fish (Noble et al, 2012;Stien et al, 2013;Noble et al, 2020). Especially fin injuries are common in aquaculture, impacting fish performance and health and are as such generally accepted as indicator for impaired welfare of fish (Latremouille, 2003;Ellis et al, 2008;Noble et al, 2012;Klíma et al, 2013;Stien et al, 2013;Noble et al, 2020). The impact of fin injuries on welfare depends on severity, type, and number of fins injured, as the latter significantly impact swimming ability, increase energy demand, reduce growth, increase susceptibility to infection, and can even result in mortality (Latremouille, 2003;Ellis et al, 2008;Noble et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the third dorsal fin was already eroded by the start of the experiment and it may possibly heal and regenerate more rapidly than the other fins. Fish are capable of healing damaged fins and regenerated fins have been shown to have the same shape and size as the original fin of the fish (Atta, Abdel‐karim & Elsheikh ; Klíma, Kopp, Hadašová & Mareš ). By using the same data, Nielsen et al .…”
Section: Discussionmentioning
confidence: 99%